On-site treatment of avalanche victims: Scoping review and 2023 recommendations of the international commission for mountain emergency medicine (ICAR MedCom). (March 2023) - Pasquier, M.; Strapazzon, G.; Kottmann, A.; Paal, P.; Zafren, K.; Oshiro, K.; Artoni, C.; Van Tilburg, C.; Sheets, A.; Ellerton, J.; McLaughlin, K.; Gordon, L.; et al.
Abstract: Introduction: The International Commission for Mountain Emergency Medicine (ICAR MedCom) developed updated recommendations for the management of avalanche victims. Methods: ICAR MedCom created Population Intervention Comparator Outcome (PICO) questions and conducted a scoping review of the literature. We evaluated and graded the evidence using the American College of Chest Physicians system. Results: We included 120 studies including original data in the qualitative synthesis. There were 45 retrospective studies (38%), 44 case reports or case series (37%), and 18 prospective studies on volunteers (15%). The main cause of death from avalanche burial was asphyxia (range of all studies 65–100%). Trauma was the second most common cause of death (5–29%). Hypothermia accounted for few deaths (0–4%). Conclusions and recommendations: For a victim with a burial time ≤ 60 minutes without signs of life, presume asphyxia and provide rescue breaths as soon as possible, regardless of airway patency. For a victim with a burial time > 60 minutes, no signs of life but a patent airway or airway with unknown patency, presume that a primary hypothermic CA has occurred and initiate cardiopulmonary resuscitation (CPR) unless temperature can be measured to rule out hypothermic cardiac arrest. For a victim buried > 60 minutes without signs of life and with an obstructed airway, if core temperature cannot be measured, rescuers can presume asphyxia-induced CA, and should not initiate CPR. If core temperature can be measured, for a victim without signs of life, with a patent airway, and with a core temperature < 30 °C attempt resuscitation, regardless of burial duration.